Inquiry of the Practice of Leadership in Chengguan: A Study Based on the Ethnographic Research of Z City - Li, Hua; Li, Yifan (Frontiers in Psychology, 2022)
Chengguan, the Urban Administrative Law Enforcement Bureau, has been criticized for its dismal public image and poor job performance. Based on an ethnographic case study in Z City, we analyzed the type of leadership that results in passive work performance in Chengguan, and we examined whether any leadership style can be used to improve Chengguan's image and performance. We developed a new leadership ontology of CNP (Cognition–Normalization–Performance) on this foundation, and ethnographic research was conducted in three phases: leader's cognition, followers' normalization, and organization performance. Several implications were drawn. Leader selection should be cautious and can be improved by studying the leader's traits and behavior. This is done by investigating candidates' leadership career paths, trait characteristics, motive profiles, and other qualities. It is useful to change leaders by strengthening followers' unity and cohesion by setting up a labor union, youth federation, women's federation, and other groups. A leader should be selected among individuals who have completed leadership training as opposed to appointing one from outside the organization. On the one hand, the superior should help to improve the leadership environment (context), supervise problems in the organization's operation and performance, and track changes over time. On the other hand, the leader can also provide the followers with a flexible and adaptive place of work.